Legal Aspects Of Afghanistan Accession To The World Trade Organization - Ahmad Haneef Haneef; Abdul Malik Sidiqi (CV. AFDIFAL MAJU BERKAH, 2024)
Afghanistan as a country surrounded by land and involved in successive wars, has turned into a purely consumer country, and at the same time, it has rich mines and many potential economic facilities, it is in dire need of international economic partners to be able to meet the challenges may the economy succeed in its own way. A clear example of such an international partner is the World Trade Organization (WTO), which is known as the largest authority facilitating international trade around the world. According to such specifications of the WTO, Afghanistan submitted its membership application to the organization in November 2004. In December, 2015, the ministerial conference of the organization has been accepted the membership of Afghanistan which was officially completed in on July 29, 2016. The research is a qualitative study with the descriptive-analytical method and the data has been collected from the popular academic articles, books and national and international documents, related to the issue. Consequently, the research found that accession of Afghanistan to the WTO had many legal aspects and challenges, which are explained in this article. The advantages and disadvantages of Afghanistan’s membership mostly related to the economic and financial policies of the government and the performance of the managers of this important field, and its consequences and practical results, will determine the future.